Developing and Evaluating a Hot Water-Assisted Extractor for Making Instant Drink from Date Kernels Powder - Milad Felegary; Kazem Jafarinaeimi; Hamid-Reza Akhavan (Biomechanism and Bioenergy Research, 2023)
Date tree (Phoenix dactylifera L.) is one of the oldest cultivated trees in the world, which grows in tropical and subtropical regions. This product is one of the most important products of the Middle East and North Africa. In this research, date kernel extract (DKE) was produced from date kernel powder in a hygienic and mechanized process. Hot water-assisted extraction of compounds from date kernel powder was carried out in the chamber system made in the research. The experiments were conducted using the response surface method (RSM)-central composite design. Independent variables included temperature and time of processing and liquid-to-solid ratio. The obtained solutions were dried by a vacuum rotary evaporator and some quality characteristics (total soluble solids (TSS), antioxidant activity, total phenolic content (TPC), melanoidins, and sensory properties) were evaluated. The results showed that the triple factors of temperature, time and liquid-to-solid ratio have a direct effect on the extraction efficiency, so that the increase of these factors had a significant effect on the extraction efficiency. The predicted efficiency equations for each of the above cases were significant at the 5% level and R2 was above 0.95. The results of the TSS, TPC, melanoidins and sensory attributes confirmed the high desirability of the produced DKE.